The Case - Jovanovski, Jovan; Vuksanovikj, Vladimir; Dalip, Мetin; Regjepagikj, А (Faculty of physical education sport and health, 2012)
Subject of this study is the strength endurance of a respondent at the age of 20 years, in context of sudden, unexpected and extreme achievement in performing deep squats repetition until failure, performed without external burden. The registered extreme achievements were being monitored for a period of one month, when the subject was not under strength programme. Significant differences were registered in the repetition until failure between the first, second and the third experimental measuring. The experiment was designed by applying relevant physiological and motor parameters, appropriate for this type of studies.
Keywords: motivation; endurance; lactates; anaerobic threshold; repetition until failure; deep squat; metabolic and mechanical strength; genes